Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 2020 International Conference on Multimodal Interaction 2020
DOI: 10.1145/3382507.3418885
|View full text |Cite
|
Sign up to set email alerts
|

Toward Adaptive Trust Calibration for Level 2 Driving Automation

Abstract: Figure 1: Simulation environment of our user study with augmented reality (AR)-based information presentation. The goal of this research is to calibrate a driver's trust in driving automation through AR-based information while avoiding increased driver workload.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 44 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…However, these models have linear assumptions of human trust behaviors. Considering these limitations, machine learning models became popularly used to predict driver trust, such as support vector machine (SVM), K neighbor (KNN), and quadratic discriminant analysis (QDA) (32)(33)(34)(35). For instance, Akash et al (33) applied electroencephalography (EEG) and GSR to identify users' trust in an obstacle detection system (as used in AVs) by the QDA.…”
Section: Trust Estimation and Recognition Model In Automated Vehicle ...mentioning
confidence: 99%
“…However, these models have linear assumptions of human trust behaviors. Considering these limitations, machine learning models became popularly used to predict driver trust, such as support vector machine (SVM), K neighbor (KNN), and quadratic discriminant analysis (QDA) (32)(33)(34)(35). For instance, Akash et al (33) applied electroencephalography (EEG) and GSR to identify users' trust in an obstacle detection system (as used in AVs) by the QDA.…”
Section: Trust Estimation and Recognition Model In Automated Vehicle ...mentioning
confidence: 99%
“…Wang et al (2020) showed how guidance can be displayed using colored lanes on the windshield. Other information that can be presented in AR can include navigation arrows and bounding boxes for the scene objects (Liu et al, 2021;Akash et al, 2020). For route guidance, one can also superimpose a lead vehicle to help guide the human driver on their route.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the possible solutions to calibrate trust. These include paradigms that anticipate human behaviors-such as trust-and inform humans to make optimal choices [7], [8], [9]. However, a primary challenge for such an approach is quantitatively predicting human trust in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is challenging to obtain self-reports repeatedly without interrupting the task. As an alternative, recent works have developed dynamic models to capture human trust and estimate it in real-time [13], [14], [15], [9]. There are two approaches for developing such models: a general model for the whole population and a personalized model for each individual to account for individual differences [16].…”
Section: Introductionmentioning
confidence: 99%